An unusual presentation of a patient with covid-19 infection—lemierre’s syndrome - ASYA, ORHAN (My University, 2022)
Lemierre’s syndrome refers to septic thrombophlebitis of the internal jugular vein that is rarely seen after an oropharyngeal infection. We present the case of a 64-year-old female patient with Covid-19 infection and Lemierre’s syndrome. Contrast-enhanced computed tomography of the neck revealed thrombosis in the left internal jugular vein and non-contrast-enhanced computed tomography of the thorax was consistent with Covid19 infection. The patient was immediately hospitalized. Systemic antibiotics, anticoagulation therapy, and favipiravir treatment for Covid-19 infection were started. Unfortunately, the patient died about two weeks after hospitalization. To the best of our knowledge, this is the first case of Lemierre’s syndrome and Covid-19 overlap. Clinical suspicion of Lemierre’s syndrome is important for rapid diagnosis. During this Covid-19 pandemic, we should keep in mind that any patient may have Covid-19 infection. In addition to the patient’s primary disease, with clinical or laboratory suspicion of Covid-19 infection, diagnostic tests for it should also be conducted.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Lemierre’s syndrome; internal jugular vein thrombosis; Covid-19 infection; deep neck infection